Effets De La Fertilisation Sur Les Nématodes Parasites Et Le Rendement En Rhizomes Frais Du Gingembre, Zingiber officinale Rosc - Alèdi, Assih; Amen, Nenonene Yawo; Atti, Tchabi; Rodrigue, Fiaboe Kokou; Pikassalé, Akantetou Komla (European Scientific Journal, ESJ, 2018)
Ginger, Zingiber officinale is one of the most cultivated spices in the world. Therefore its production is often subject to high pest and disease pressures, particularly that of plant parasitic nematodes. For the sustainable management of parasitic nematodes of ginger, a trial was conducted at Agronomic Research Station of the Graduate School of Agronomy at the University of Lomé to assess the efficacy of some organo-mineral fertilizers on parasitic nematodes. An organic manure based on house waste valorization in three doses (0tha -1 ; 15tha-1 and 25tha-1 ) and five mineral fertilizer formulations from simple mineral fertilizers (Urea 46%, the chloride of potassium and the triple superphosphate): N0P0K0; N45P15K60; N70P50K50; N90P30K100 and N125P90K100) were used according to a split plot design. The inventory of the nematodes permitted to count five genders of nematodes: Meloidogyne; Xiphinema; Longidorus; Helicotylenchus and Pratylenchus. The results indicated that an input of 25 tons of organic manure associated with mineral fertilizer of N70P50K50 and N125P90K100 reduce nematode density by up to 58.62% in roots and 95.88% in soil compared to the treatment without manure and mineral fertilizer. The yield of fresh rhizomes vary from 2.9 to 7.7 t/ha with little statistically effects of the manures. This study reveals that nematodes constitute a serious phytosanitary problem for ginger and that the contribution of organo-mineral fertilization makes it possible to reduce the density of nematodes under ginger.